Studies on the reproductive performance of Ethiopian sheep by means of an Enzyme Immunoassay Technique; a review - Mukasa-Mugerwa, E.; Mutiga, E.R.; Girma, A. (Commonwealth Scientific and Industrial Research Organisation, 1992)
Reviews aspects of several studies on the reproductive performance of Ethiopian Menz sheep in which plasma progesterone concentrations were monitored. The radioimmunoassay (RTA) technique has been used for determining progesterone concentration in blood and milk (Pope et al 1976; Holdsworth 1980), but it requires the use of radioisotopes, expensive equipment and special arrangements for the disposal of waste. In contrast, the enzyme-linked immunosorbent assay (ELISA) is equally accurate, safer and uses less costly equipment. Moreover, commercial ELISA kits are available and some of these can be used qualitatively, making the procedure suitable for field application in the tropics. Table 1 gives summaries of the effect of nutrition and treatment for endoporasites on the trait. Altogether, 50 oestrus period were either detected by rams or confirmed from progesterone profiles.